Derivation and Identification of Motor Neurons from Human Urine-Derived Induced Pluripotent Stem Cells - Huan Yi; Bingbing Xie; Ben Liu; Xuan Wang; Li Xu; Jia Liu; Min Li; Xiufeng Zhong; Fuhua Peng (Stem Cells International)
Induced pluripotent stem cells (iPSCs) have provided new opportunities for motor neuron disease (MND) modeling, drug screening, and cellular therapeutic development. Among the various types of iPSCs, urine-derived iPSCs have become a promising source of stem cells because they can be safely and noninvasively isolated and easily reprogrammed. Here, for the first time, we differentiated urine-derived iPSCs (urine-iPSCs) into motor neurons (MNs) and compared the capacity of urine-iPSCs and cord-blood-derived iPSCs (B-iPSCs) to differentiate into MNs. With the use of small molecules, mature MNs were generated from urine-iPSCs as early as 26 days in culture. Furthermore, in coculture with muscle cells, MNs projected long axons and formed neuromuscular junctions (NMJs). Immunofluorescence and PCR confirmed the expression levels of both MN and NMJ markers. The comparison of the ratios of positive labeling for MN markers between urine-iPSCs and B-iPSCs demonstrated that the differentiation potentials of these cells were not significantly different. The abovementioned results indicate that urine-iPSCs are a new, promising source of stem cells for MND modeling and further cellular therapeutic development.